The Influence of The Environment, Tariffs and Facilities on the Satisfaction of Flat Residents Under the Management of BP Batam With Service Quality as Variable Intervening - YUNUS, Andi; NGALIMAN, Ngaliman; SAJIYO, Sajiyo (PT Keberlanjutan Strategis Indonesia, 2025)
This research analyzes the influence Environment, Tariffs And Facilities Towards Satisfaction of Flat Residents Under the Management of Mr Batam With Service Quality As an Intervening Variable. Based on data from BP Batam in 2023, there are kabil flats 530 reports, yellow face flats with 613 reports, Batu Ampar flats with 610 reports, Sekupang flats with 487 reports, and Tanjung Uncang flats with 501 reports. This shows that there are still many flat residents who experience problems when inhabiting flats. Using primary data from 176 Flat Residents Under the Management of Mr Batam, this research found that Environment Nah has a direct significant effect on Flat Residents' Satisfaction, instead Rates and Facilities proven to have influence yang significant to Flat Residents' Satisfaction, additionally the Environment has an insignificant influence on Service Quality, but Trif and Facilities have a significant influence on Service Quality. Service Quality has a significant effect on the satisfaction of flat residents. The indirect influence of the environment has an insignificant influence on the satisfaction of flat residents through service quality, but rates and facilities have a significant influence on the satisfaction of flat residents through service quality. The proposed recommendation is to focus on scaling up Flat environment and improve the quality of services provided to flat residents.